α1-Blockers and 5α-Reductase Inhibitors Are the Most Recommended Drugs in Treating Benign Prostatic Hyperplasia: An Evidence-Based Evaluation of Clinical Practice Guidelines - Xu, Xiao-Feng; Liu, Guo-Xiong; Zhu, Cong; Qiao, Xi-Min; Yu, Shao-Fu; Deng, Tong; Jin, Ying-Hui (Frontiers in Pharmacology, 2020)
Objective: To systematically evaluate the quality of clinical practice guidelines (CPG) for medically treating benign prostatic hyperplasia (BPH), and to compare the context of recommendations in order to provide references for clinical application. Methods: We searched databases of National Guideline Clearinghouse(NGC), Guidelines International Network(GIN), National Institute for Health and Clinical Excellence(NICE), Scottish Intercollegiate Guidelines Network(SIGN) and World Health Organization(WHO), PubMed, Embase, CNKI, VIP, WanFang Data, CBM and Medlive from their establishment to October 13, 2019 to collect evidence-based guidelines and/or consensus on BPH. Method quality of included guidelines was assessed according to the Appraisal of Guidelines for Research and Evaluation II(AGREE II) instrument, and differences and similarities among recommendations were compared. Results: A total of 22 guidelines were included, of which 8 were updated versions. According to the AGREE II instrument, the median score of scope and purpose, stakeholder involvement, rigour of formulate, clarity of presentation, applicability, and editorial independence was 71.5%, 41%, 25%, 64%, 18%, and 28%, respectively. Based on recommendations for medical treatment, almost all guidelines recommended α1-blockers and 5α-reductase inhibitors, and most guidelines also recommended muscarinic receptor antagonists. In terms of drug combination therapy, most guidelines recommended “α1 blockers and 5α-reductase inhibitors”, and some guidelines also recommended “α1 blockers and muscarinic receptor antagonists”. Conclusion The recommendations from different guidelines were basically similar, only showing conflicts in some areas. The quality of included guidelines remains to be unified, and their context can provide valuable implications for development or improvement.